Pengaruh Komitmen, Kualitas Sumber Daya Manusia, Gaya Kepemimpinan Terhadap Kemampuan Penyusunan Anggaran pada Pemerintah Kota Manado - Rumenser, Peggy (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2014)
The implementation of the local government can not be separated from the budget. In Regulation No. 13 of 2006, the draft budget work units contained in a document called the Draft Budget Unit (Rask). Rask standard includes expenditure analysis, a benchmark of the performance of standard costs as the principal instrument in the budget performance. The budget is important because it is used in the allocation of funds for the implementation of local government activities. In budgeting involvement of various work units (SKPD) in Manado City Government is indispensable. This is to improve the effectiveness and efficiency of governance and public service. This study aims to analyze Effect of Commitment, Quality of Human Resources, Leadership Style, to the ability of Local Government Budgeting in Manado. Sources of data in this study are primary data and secondary data in the form of a questionnaire. The population in this study is the employee on education (Department and Agency) Manado, and in this study the sampling method used was judgment sampling, the sample in this study is the Secretary, Head of Division (third tier). Data used in this study is mainly qualitative data were quantified by using multiple regression analysis. To test the quality of the data with validity and reliability. Besides testing the classical assumption of normality, multicollinearity and heteroscedasticity. The research proves that in partial Commitment, Quality of Human Resources does not affect the ability of Budgeting in Local Government Leadership Style Manado while variable positive effect on the ability of Local Government Budgeting in Manado.